Female Genital Mutilation/Cutting: A Conceptual Discussion - Ndasi , Darlene Mwende; Adusei-Asante, Kwadwo (Advances in Social Sciences Research Journal, 2019)
Female genital mutilation/cutting (FGM/C) is a dangerous practice that predates all religions and perpetrated on children for various reasons in various cultural and global contexts, causing adverse lifelong health consequences including sexual, physical and psychological problems for the survivors. Even so, there appears to be no documented work that brings together the major conceptual blocks on FGM/C, a gap this paper seeks to begin to fill. This paper summarises some major concepts on FGM/C as a resource and evaluates key evidence on the practice. While the practice of FGM/C is highly concentrated in Africa, the practice is spread out globally with a shift towards its medicalization among migrant communities and traditional settings. A focus of this paper is to propagate awareness and polarise debates to bring to an end to the practice of FGM/C globally.